IRE transactions on bio-medical electronics / [mikrofilem] - Institute of Radio Engineers Professional Group on Medical Electronics (New York : Institute of Radio Engineers. Professional Group on Medical Electronics, 1961)
Library has : vol.BME8, no.1 (Jan. 1961) - vol.BME9, no.4 (Oct. 1962)